2011
DOI: 10.1186/1471-2334-11-130
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility of invasive yeast isolates in Italy: the GISIA3 study in critically ill patients

Abstract: BackgroundYeasts are a common cause of invasive fungal infections in critically ill patients. Antifungal susceptibility testing results of clinically significant fungal strains are of interest to physicians, enabling them to adopt appropriate strategies for empiric and prophylactic therapies. We investigated the antifungal susceptibility of yeasts isolated over a 2-year period from hospitalised patients with invasive yeast infections.Methods638 yeasts were isolated from the blood, central venous catheters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
10
0
4
Order By: Relevance
“…Twenty out of 142 clinical isolates of C. albicans collected during an Italian National survey on invasive fungal infection in ICU [16] were used to assess whether biofilm production can be a hallmark of virulence in vivo. The 20 strains were selected for further experiments based on their high reproducibility or constant incapacity to form biofilm in vitro.…”
Section: • • C Albicans Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty out of 142 clinical isolates of C. albicans collected during an Italian National survey on invasive fungal infection in ICU [16] were used to assess whether biofilm production can be a hallmark of virulence in vivo. The 20 strains were selected for further experiments based on their high reproducibility or constant incapacity to form biofilm in vitro.…”
Section: • • C Albicans Isolatesmentioning
confidence: 99%
“…The primary aim of this work was to assess the pathogenic role of filamentation and biofilm formation in a subset of C. albicans isolates collected from cases of invasive infections in patients hospitalized in medical or surgical ICU [16]. To simulate invasive infections, the virulence potential of biofilm was determined in the G. mellonella model comparing biofilm producer (BP) and nonproducer (NP) invasive C. albicans strains.…”
mentioning
confidence: 99%
“…Nevertheless, in the DGP wards, the increase in NCA strains followed those found in the other medical specialities [15, 16, 20, 21, 26, 29, 34, 54, 55, 61, 64, 66]. A summary of the distribution of Candida species in epidemiological surveys of the last decades was given in [6668].…”
Section: Resultsmentioning
confidence: 99%
“…2,27 This therapeutic choice could have been made because of the previous exposure of the patient to azoles, and because two of the three available echinocandins were still having MIC values compatible with the proposed MIC interpretive breakpoints for susceptibility at that time. 28,29 We have to consider that often physicians initiate antifungal treatment without regard to in vitro data, which arrive too late and when the patient starts to improve. 2,11 In a retrospective study, Shields and co-workers suggested that the FKS genotype is a better indicator of echinocandin therapeutic failure than MIC alone.…”
Section: Discussionmentioning
confidence: 99%